Pengembangan media powerpoint interaktif pada pembelajaran tematik di sekolah dasar - Inna Novia Purwaningsih; Trisniawati; Taryatman, Taryatman; Ardhian, Trio (Universitas Sarjanawiyata Tamansiswa, 2024)
This research and development was conducted at SD N 1 Joton. Interactive PowerPoint Learning Media in Elementary School Thematic Learning aims to develop thematic learning media in grade II. This research and development use the ADDIE model which consist of analysis, design, development, implementation and evaluation. The method used is descriptive kuantitative. Data collection techniques used interviews and questionnaires. The research instrument, in the form of a questionnaire, is used to validate learning media. The validators consist of media experts and material experts. The result of the validation instrument are calculated as an average. The validity criterion is if media gets a score between 3,4 < 4,1 which is included in the valid category or 4,2 < 5 which is included in the very valid category. The results of the research are: (1) The product meets the very valid criteria. This can be seen from the validation results of interactive PowerPoint learning media in thematic learning in class II elementary schools by material experts and media experts. (2) Obtaining the overall average score obtained by the first and second material experts was 4.90 and was included in the